Efficient Total Syntheses of (−)-Colombiasin A and (−)-Elisapterosin B: Application of the Cr-Catalyzed Asymmetric Quinone Diels-Alder Reaction - Boezio, Alessandro A.; Jarvo, Elizabeth R.; Lawrence, Brian M.; Jacobsen, Eric N. (Angewandte Chemie International Edition, 2005)
A made‐to‐order asymmetric catalytic reaction was applied in the key quinone Diels–Alder step of the total syntheses of the title compounds (see scheme for the synthesis of colombiasin A). The reaction was highly regio‐ and diastereoselective.